Pengaruh Inflasi dan Angka Pengangguran terhadap Pertumbuhan Ekonomi Melalui Tingkat Kemiskinan 7 Kota/Kabupaten di Jawa Timur - Farah Salsabila Firda, Hayyu; Fakhril Ma’ruf, Muhammad; Yuliana, Indah; Sri Rahayu, Yayuk (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The purpose of this study is to analyze the relationship between inflation, unemployment rate, poverty rate and economic growth in East Java province. The introductory chapter focuses on the economic challenges of developing countries, particularly those related to poverty, inflation, and economic growth. The research method uses a descriptive quantitative approach with hypothesis testing using t-values. Data for his seven cities/districts in East Java province were collected by the Central Bureau of Statistics from 2012 to 2022. The results of classical assumption testing indicate that the data are normally distributed, with no multicollinearity, autocorrelation, or heteroscedasticity. The results of the hypothetical analysis show that inflation has no significant impact on poverty, but unemployment has a significant negative impact. Inflation does not have a direct impact on economic growth, but unemployment rate has a negative impact on economic growth. Poverty level does not have a significant impact on economic growth. The conclusion emphasizes the importance of controlling the unemployment rate to reduce poverty and improve economic growth in East Java. Although inflation does not have a direct impact on economic growth, its stability is still important. Suggestions for further research include considering additional variables and gaining a deeper understanding of regional economic dynamics.